2022
DOI: 10.1056/nejmoa2118946
|View full text |Cite
|
Sign up to set email alerts
|

Protection and Waning of Natural and Hybrid Immunity to SARS-CoV-2

Abstract: Background Infection with severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) provides natural immunity against reinfection. Recent studies have shown waning of the immunity provided by the BNT162b2 vaccine. The time course of natural and hybrid immunity is unknown. Methods Using the Israeli Ministry of Health database, we extracted data for August and September 2021, when the B.1.617.2 (delta) variant was predominant, on all persons who had been previously inf… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

44
334
0
7

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 368 publications
(385 citation statements)
references
References 25 publications
44
334
0
7
Order By: Relevance
“…This held true in individuals with efficient neutralizing responses and contained disease manifestations ( Figure 4 D and Supplementary Figure S2B ). This feature may either reflect a more targeted humoral response induced by vaccination over natural infection, or the superiority of hybrid immunity over immunity elicited by infection alone [ 36 , 93 , 100 , 101 , 102 ]. The observation that BTI patients with higher anti-N antibody levels had the highest neutralizing activity argues in favor of the second hypothesis.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This held true in individuals with efficient neutralizing responses and contained disease manifestations ( Figure 4 D and Supplementary Figure S2B ). This feature may either reflect a more targeted humoral response induced by vaccination over natural infection, or the superiority of hybrid immunity over immunity elicited by infection alone [ 36 , 93 , 100 , 101 , 102 ]. The observation that BTI patients with higher anti-N antibody levels had the highest neutralizing activity argues in favor of the second hypothesis.…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, breakthrough infection after vaccination confers some cross-protection, while Omicron BA.1 infection alone offers limited protection against pre-Omicron and against Omicron BA.2 and BA.2-related sublineages [ 92 , 95 , 96 ]. Hybrid immunity appears to cross-protect more efficiently than infection or vaccination individually and seems to be more durable [ 36 , 49 , 100 , 101 , 102 , 120 , 121 ], likely as a result of antibody affinity maturation [ 67 , 99 , 122 , 123 ]. In our case, BTI patients were not followed longitudinally and the time elapsed since infection was not known.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, some studies have reported discrepant results. For instance, an Israeli study performed during the B.1.617.2 (delta) variant wave of the pandemic, examined the waning of natural immunity in a recovered, unvaccinated cohort [ 96 ]. After controlling for ethnicity and exposure risk, the number of confirmed infections per 100,000 person-days at risk ranged from 14.2 in 16–39 year-old persons infected 4–6 months previously to 34.9 in individuals infected more than 1 year previously.…”
Section: Sars-cov-2 Vaccine Response In the Elderlymentioning
confidence: 99%
“…After controlling for ethnicity and exposure risk, the number of confirmed infections per 100,000 person-days at risk ranged from 14.2 in 16–39 year-old persons infected 4–6 months previously to 34.9 in individuals infected more than 1 year previously. In the ≥60 year category, the equivalent number of confirmed infections per 100,000 person-days at risk ranged from 4.2 to 12.4 [ 96 ].…”
Section: Sars-cov-2 Vaccine Response In the Elderlymentioning
confidence: 99%
“…Similar to vaccine-induced and infection-induced immunity, hybrid immunity also wanes over time. 4 , 5 , 6 , 7 Unsurprisingly, omicron can evade hybrid immunity acquired in the pre-omicron era. 5 , 6 Nevertheless, hybrid immunity seems to protect well against severe COVID-19 caused by omicron, at least in young populations.…”
mentioning
confidence: 99%